Co-creating the pitch: An exploration of the role of traditions on co-creation in European soccer - Eric Hungenberg; Mark Slavich; Ricardo Cayolla (Journal of Applied Sports Management, 2024)
As the sport of soccer continues to grow throughout the world – and particularly into North America – the current study assessed the causal effect fans’ sensory traditions have on co-creation. Data were collected by intercepting Portugese and Spanish soccer attendees outside of the stadium prior to the match’s start. A total of 282 useable surveys were retrieved from fans during the 2022-23 seasons. Path modeling results indicate that traditions relating to aesthetics, sound, and beverage provided the greatest means to co-create experiences for attendees. The study’s results align with previous research within retail and sport exhibiting the positive impact of the sensory experience on social, psychological, and behavioral outcomes (Clark et al., 2012; Hungenberg et al., 2020). Furthermore, the findings provide support that sensory experiences wielding heightened levels of co-creation for fans contribute positively to merchandise spending and arrival time. This is meaningful as sport organizations continue to seek marketing strategies that will overcome the widespread media platforms that have made consuming sport remotely so accessible.
Keywords: Sensory Marketing; Sport Traditions; Soccer; Co-Creation